The Efficacy of Quercetin in Cardiovascular Health - Ward, Natalie; Bondonno, N.; Bondonno, C.; Hodgson, J.; Croft, K. (2015)
Cardiovascular disease is a major cause of death worldwide despite the majority of its risk factors being preventable and treatable. The results of numerous epidemiological studies suggest that a diet rich in fruits and vegetables affords protection against CVD, and this may be attributed, in part, to the flavonoid quercetin. The aims of this review are to summarise the current knowledge on the bioavailability and metabolism of quercetin as well as discuss the current evidence behind the potential mechanisms by which quercetin exerts its cardioprotective effects. This review summarises key human studies administering quercetin that have been published to date. Although interesting results have been seen in animal and cell culture studies, in general, these have not been replicated in human trials. Several studies have, however, shown that quercetin can reduce blood pressure in hypertensive patients. The exact mechanisms are yet to be elucidated. Further studies are required to investigate the use of quercetin as a cardioprotective treatment, in particular long-term and dose–response studies.